Diabetes-Related Patient Outcomes through Comprehensive Medication Management Delivered by Clinical Pharmacists in a Rural Family Medicine Clinic - Jarred Prudencio; Michelle Kim (MDPI AG, 2020)
Two clinical pharmacy faculty members from a college of pharmacy provide comprehensive medication management in a rural family medicine clinic. The data was assessed for patients with diabetes managed by the pharmacists from 1 January 2017 through to 31 December 2019 to determine the service's impact on patient outcomes. The primary outcome of this study is the change in the goal attainment rates of the three clinical goals of hemoglobin A1c, blood pressure, and appropriate statin therapy after pharmacist intervention. A total of 207 patients were included. At baseline, the patients had an average of 1.13 of the three goals met, improving to an average of 2.02 goals met after pharmacist intervention (p < 0.001). At baseline, 4.8% of the patients had met all three clinical goals, improving to 30.9% after pharmacist intervention (p < 0.001). There were significant improvements for the individual goal attainment rates of hemoglobin A1c (24.15% vs. 51.21%, p < 0.001), blood pressure (42.51% vs. 85.51%, p < 0.001), and appropriate statin therapy (45.89% vs. 65.70%, p < 0.001). This data adds to the evidence supporting the integration of clinical pharmacists into primary care clinics to improve patient outcomes related to diabetes.